Dyadic Influence of Adverse Childhood Experiences: Counseling Implications for Mental and Relational Health. (10th December 2020) - Wheeler, Naomi J.; Regal, Rachel A.; Griffith, Sandy‐Ann M.; Barden, Sejal M.
Abstract : Adverse childhood experiences (ACEs) predict physical and mental health. We examined dyadic differences in intimate partner relationship health by ACE score among couples with low to moderate income enrolled in a relationship education program. Overall, we found a high prevalence of ACEs, disproportionate representation in the highest risk ACE group, and a significant effect between ACEs and indicators of mental and relational health. Implications for counselors include support for an ACE‐informed approach to couples counseling services, as well as a holistic and systemic view of mental and relational health.